Implementasi Flipped Classroom di SMA Al Muayyad Surakarta Pada Pembelajaran Fisika Gerak Harmonik Sederhana - Ridho, Malik Rosyid; Raharjo, Dwi Teguh; Supurwoko, Supurwoko (Universitas Sebelas Maret, 2023)
The Classroom Action Research conducted at Al Muayyad High School to improve students' cognitive abilities in terms of student activeness by using a flipped classroom learning model. The subjects of this research are 30 students. Data collection techniques are carried out using cognitive test instruments, observation sheets, and interviews both online and offline. The student activeness studied consists of 5 aspects, namely Visual, Oral, Listening, Writing and Mental. Student activeness data was collected using observation instruments and student cognitive ability data was collected using cognitive test instruments. The action was carried out in 2 cycles, each cycle consisting of planning, action, observation and reflection stages. Aspects of student visual activeness in the pre-cycle amounted to 25%; cycle I amounted to 66%; cycle II amounted to 88%. The aspect of students' oral activeness at pre-cycle was 38%; cycle I was 48%; cycle II was 64%. The aspect of student listening activity in the pre-cycle was 60%; cycle I was 70%; cycle II was 88%. The aspect of student writing activity in the pre-cycle was 45%; cycle I was 61%; cycle II was 80%. The aspect of students' mental activeness in the pre-cycle was 35%; cycle I was 67%; cycle II was 86%. While the results of students' cognitive abilities that were completed at the pre-cycle were 3%; cycle I was 14%; cycle II was 90%. Learning with a flipped classroom can improve students' cognitive abilities in terms of the activeness of class X students of SMA Al Muayyad Surakarta.